Unemployment Risk and Debt Contract Design - Yehuda, Nir; Armstrong, Christopher S.; Cohen, Daniel; Zhou, Xiaolu (The Accounting Review, 2023)
ABSTRACT We examine how firms’ contractual relationships with their employees affect the design of their debt contracts, and the use of financial covenants in particular. Viewing the firm as the nexus of both explicit and implicit contractual relationships, we argue that managers cater to their employees’ preferences when negotiating contractual terms with creditors. We argue that an increase in unemployment-insurance benefits reduces employees’ cost of job loss, which, in turn, allows managers to take more risk. First, we show that more generous benefits are associated with a higher operating leverage, operating cash flow volatility, and product-development frequency. We then find that loans initiated following an increase in unemployment-insurance benefits include a higher proportion of performance, rather than capital covenants. Overall, our study demonstrates how the design of debt contracts changes in response to arguably exogenous changes in employees’ collective tolerance—and, in turn, managers’ preferences—for risk. JEL Classifications: M41; G32; J60.